PERAN CITRA MEREK MEMEDIASI KEUNGGULAN PRODUK DENGAN MINAT BELI SEPEDA MOTOR YAMAHA NMAX - Putri, Ni Nyoman Inten Kemara Septiana; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 7 No 10 (2018), 2018)
Yamaha can indirectly affect a person in making purchases, the more product advantages and high brand image owned by a product will be more attractive to most people. This research was conducted in Kuta Village. The number of samples taken is 110 samples with purposive sampling method. The analysis technique used is path analysis (Path analysis). Based on the results of the analysis found that product advantages have a positive and significant effect on brand image and buying interest, brand image has a positive and significant impact on buying interest, and brand image plays a role in mediating the effect of product superiority on buying interest. Advice for the company to continue to develop products owned to have excellence and can create a brand image for the product generated so as to help in increasing sales.